2019
DOI: 10.1021/acs.analchem.9b04922
|View full text |Cite
|
Sign up to set email alerts
|

Tale of Two Alkaloids: pH-Controlled Electrochemiluminescence for Differentiation of Structurally Similar Compounds

Abstract: Electrochemiluminescence (ECL) has increased in popularity as a result of its inherent advantages, including but not limited to portability, simplicity of use, and low reagent consumption. However, its significant advantages are often over shadowed as a result of its limited specificity. ECL emissions are intrinsically broad and lack the definition of other available analytical techniques. Furthermore, species with similar functional groups have almost identical electrochemical behavior and thus typically emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…The major challenge, highlighted by this contribution is the need to discriminate between structurally similar compounds. This has been examined for other illicit substances [16][17][18][19] but research on SCs is still limited in this area. In addition, street samples of SCs are likely to contain other illicit substances, notably amphetamine type substances (ATS).…”
Section: Resultsmentioning
confidence: 99%
“…The major challenge, highlighted by this contribution is the need to discriminate between structurally similar compounds. This has been examined for other illicit substances [16][17][18][19] but research on SCs is still limited in this area. In addition, street samples of SCs are likely to contain other illicit substances, notably amphetamine type substances (ATS).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is need to develop a rapid, inexpensive detection method for detection of 5-HT. Electrochemical methods have been highlighted as a viable method to address these points and develop a rapid, portable detection of a range of analytes 15 17 including 5-HT determination primarily due to their simple design, cost effectiveness, dynamic response, good selectivity, sensitivity 18 , etc. The combinations of these approaches with different NCs for electrochemical 5-HT sensing studies have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, this single luminophore approach often prevents the successful differentiation of structurally similar compounds, which typically interact with the complex via analogous mechanisms producing emission within the same potential regions. 11,21,22 Employment of multi-luminophore sensors utilising several different metal complex luminophores as well as pH-controlled emission offer viable approaches to tackle the limited specificity associated with ECL techniques. Prior work has demonstrated the ability to exploit differences in the relationship between pH and luminescence intensity, to produce a system whereby two structurally similar species, atropine and scopolamine, could both be identified within a mixed sample.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has demonstrated the ability to exploit differences in the relationship between pH and luminescence intensity, to produce a system whereby two structurally similar species, atropine and scopolamine, could both be identified within a mixed sample. 21 This involved an "emission-on/emission-off" system, whereby sample pH was adjusted to prevent emission from atropine, whilst recording that of scopolamine. 21 Although this initial study showed promise, it relied upon an in-depth knowledge and understanding of the relationship between the target analytes ECL signal with pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation